Teacher feedback, disciplinary climate, student self-concept, and reading achievement:A multilevel moderated mediation model. (June 2022) - Ma, Lihong; Xiao, Leifeng; Hau, Kit-Tai
Abstract: Research has confirmed the importance of teacher feedback on student learning. The mechanism of how they are related, however, is not clear enough. In this study, we explored this relation with 60, 501 fifteen-year-old students from collectivistic and individualistic cultures in PISA 2018. Importantly, we examined the possible mediating role of reading self-concept and the moderating role of disciplinary climate at both student level and school level in multi-level structural equation models (MSEM). Results demonstrated that the association between teacher feedback and reading achievement was significantly mediated via reading self-concept at student level across cultures, and this indirect effect was significant irrespective of the disciplinary climate level. Moreover, results showed that a positive disciplinary climate would facilitate the building of students' reading self-concept which subsequently would enhance their reading achievement at school level. This study has important theoretical, practical, cross-cultural, and methodological implications for teacher feedback research and student learning. Highlights: Reading self-concept mediates between teacher feedback and reading achievement at student level. The indirect effect does not change with disciplinary climate at student level. Disciplinary climate moderates between reading self-concept and reading achievement at school level.